2012
DOI: 10.1523/jneurosci.5360-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Type 1A Receptors in C1 Neurons of the Rostral Ventrolateral Medulla Modulate the Pressor Response to Aversive Stress

Abstract: The rise in blood pressure during an acute aversive stress has been suggested to involve activation of angiotensin type 1A receptors (AT 1A Rs) at various sites within the brain, including the rostral ventrolateral medulla. In this study we examine the involvement of AT 1A Rs associated with a subclass of sympathetic premotor neurons of the rostral ventrolateral medulla, the C1 neurons. The distribution of putative AT 1A R-expressing cells was mapped throughout the brains of three transgenic mice with a bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 53 publications
(60 reference statements)
3
35
1
Order By: Relevance
“…Consistent with this possibility the RVLM seems hyperreactive to angiotensin II in several hypertension models (9,83). This last evidence implicates the C1 cells perhaps more directly in the pathological process because, in the RVLM, angiotensin-1A receptors (AT1R) are predominantly expressed by these neurons (34).…”
Section: C1 Cells and Diseasementioning
confidence: 62%
“…Consistent with this possibility the RVLM seems hyperreactive to angiotensin II in several hypertension models (9,83). This last evidence implicates the C1 cells perhaps more directly in the pathological process because, in the RVLM, angiotensin-1A receptors (AT1R) are predominantly expressed by these neurons (34).…”
Section: C1 Cells and Diseasementioning
confidence: 62%
“…Restraint stress involved guiding the mouse into a cylindrical Plexi glass restrainer with a sliding back plate to confine the mouse without applying physical pressure. More detail is provided in previous publications [1,2,4,5,[22][23][24].…”
Section: Assessment Of Cardiovascular Reactivity In Response To Stresmentioning
confidence: 99%
“…The auto-power and cross-power spectra were calculated for multiple overlapping (by 50%) segments of MAP and HR using a fast Fourier transform as adapted for conscious mice [22]. The cardiac baroreflex sensitivity was estimated as the average value of the transfer gain in the frequency band between 0.3 and 0.5 Hz [22]. Baroreflex slope was considered significant if the coherence between MAP and HR across several overlapping segments in the analyzed frequency band was more than 0.4.…”
Section: Cardiovascular Variability and Cardiac Baroreceptor Sensitivitymentioning
confidence: 99%
“…Further investigations have found that NO,45 IL‐6,25 and corticotrophin‐releasing hormone and activation of the hypothalamic‐pituitary‐adrenal axis46 are directly involved in the physiological responses to CSS. The renin‐angiotensin system plays a complex role in the pressor response to CSS, with AT 1A receptors having both prohypertensive and antihypertensive roles, depending on their location 3, 33, 34, 47, 48, 49. Future research is needed to determine whether endothelium‐derived ET‐1 interacts with these other pathways or vice versa to mediate the acute pressor response.…”
Section: Discussionmentioning
confidence: 99%